Re-description of the catfish species Liobagrus kingi Tchang, 1935 (Pisces: Amblycipitidae) from the upper Chang-Jiang basin, China - Xie, Rui-Xia; Zhang, E (Zootaxa, 2018)
The identity and validity of Liobagrus kingi Tchang, 1935 remain contentious to date due to its inaccurate original description. A re-description is provided here for this species based on our examination on its type, hitherto deposited in ASIZB and available topotypic material. It is confirmed that L. kingi is a species with a serrated posterior edge of the pectoral-fin spine and distinct from the sympatrically existing species L. nigricauda. Comments on former recognitions of specimens from the upper Chang-Jiang basin as L. kingi are presented.